The Strategic Role of Islamic Law in Strengthening Entrepreneurial Character Education in The Era of The Industrial Revolution 5.0. - Ratih Pratiwi; Ubbadul Adzkiya'; Pandu Adi Cakranegara; Irsyad Kamal; Susilo Surahman (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
The purpose of the results of this study is to analyze the strategic role of Islamic law in Strengthening Education of entrepreneurial character in the era of the Industrial revolution 5.0. This research method uses qualitative with the type of liberary research. Primary data sources use books and journals in accordance with research studies. Data collection uses reference studies: relevant journals, books, websites and magazines. The findings of this study are from an Islamic legal perspective, through the analysis of the relationship between Islamic teachings and the spirit of entrepreneurship, it refers more to the words or sentences used by the Qur'an and as-Sunnah that are relevant in the era of digitalization. The industrial era 5.0 provides opportunities for creativity in developments through connectivity and digitalization. Compared to traditional systems that still rely on human capabilities in their work, the speed and efficiency of performance will be created in the process